(3eZfj GddHjH Yf cJH GdCYGQjHs - (3GHf gTGe, CHh eMeO, LeGd GdOjf, GHf gTGe, YHO Gddg Hf jhSa Hf CMeO Hf YHO Gddg, J (B761(3g` (B1360(3es
(3ChdgG (B:s
(3ChdgG(B: (3CeG HYO MeO Gddg Ydi CaVGdg (B... (3hVYJ gPG GdJUfja hJJHYJ ajg ebdGJ eSGFd GdEYQGH (B... (3heaUdGJ jSJTcdgG GdWdGH aChVMJgG hfbMJgG hCZdGWG hbYJ dLeGYI ef GdeYQHjfs
(3BNQgG (B:s
(3BNQgG(B: (3hKehO ZPG GSJYedJ aj UhQI GdMLQ GfHFJ hEf GfHFJ bGeJ ebGe MLhO hGdUhGH CfgG Mceg cMce SGFQ GdCaYGd aj Cf fajgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B4: 147s
(3cTa GdXfhf, L (B2: 1751s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs